Labeling of mesenchymal stem cells for MRI with single-cell sensitivity - Ariza de Schellenberger, Angela; Kratz, Harald; Farr, Tracy D.; Löewa, Norbert; Hauptmann, Ralf; Wagner, Susanne; Taupitz, Matthias; Schnorr, Jörg; Schellenberger, Eyk A. (Dove Medical Press, 2016)
Sensitive cell detection by magnetic resonance imaging (MRI) is an important tool for the development of cell therapies. However, clinically approved contrast agents that allow single-cell detection are currently not available. Therefore, we compared very small iron oxide nanoparticles (VSOP) and new multicore carboxymethyl dextran-coated iron oxide nanoparticles (multicore particles, MCP) designed by our department for magnetic particle imaging (MPI) with discontinued Resovist® regarding their suitability for detection of single mesenchymal stem cells (MSC) by MRI. We achieved an average intracellular nanoparticle (NP) load of .10 pg Fe per cell without the use of transfection agents. NP loading did not lead to significantly different results in proliferation, colony formation, and multilineage in vitro differentiation assays in comparison to controls. MRI allowed single-cell detection using VSOP, MCP, and Resovist® in conjunction with high-resolution T2*-weighted imaging at 7 T with postprocessing of phase images in agarose cell phantoms and in vivo after delivery of 2,000 NP-labeled MSC into mouse brains via the left carotid artery. With optimized labeling conditions, a detection rate of ~45% was achieved; however, the experiments were limited by nonhomogeneous NP loading of the MSC population. Attempts should be made to achieve better cell separation for homogeneous NP loading and to thus improve NP-uptake-dependent biocompatibility studies and cell detection by MRI and future MPI. Additionally, using a 7 T MR imager equipped with a cryocoil resulted in approximately two times higher detection. In conclusion, we established labeling conditions for new high-relaxivity MCP, VSOP, and Resovist® for improved MRI of MSC with single-cell sensitivity.